Dinamika Garis Dalam Sketsa Analisis Karya Ipe Ma' aroef Dan Fadjar Sidik - Suyasa, I Nyoman (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
It is often said that the sketch is the most authentic trail, the exit from the artists themselves. Sketches reflect not just motor work, spontaneity, but also are difficult to be released from the documentary and a biography of the artist. Sketches are personal records in the form of visual and lines as its main element. Line shape can give birth once textures, tones, shades, and a certain volume, so as to give birth to a special character or disposition of a person. Character is owned by Ipe Ma'aroef and Dawn. They had a long journey in the creative process and the line is breath in his work. Pure lines of the sketch they showed strong character, who rarely owned by the artist now.Â KeyÂ words: Dynamics, outline, sketch, Ipe Ma'aroef and Fajar Sidik